SOCIALIZATION OF GREEN BUILDING TO PREVENT COVID 19 ON THE COMMUNITY OF GAMPONG PEURADA, BANDA ACEH - Sarina Zein, Keumala Citra; Hayati, Kemala; Sukena, Ilham; Fachrurrozi, Fachrurrozi (Universitas Muhammadiyah Aceh, 2022)
Green building is a building concept designed, constructed and operated to improve the environmental, economic, health, and productivity performance to be better than conventional buildings. The achievement of the green building in general can be seen from several standards; energy efficiency, indoor environmental quality, thermal comfort, health and productivity of building users. In May 21, data from Syiah Kuala sub-district showed that the number of people exposed to Covid 19 were increased in Peurada village and its declared as red zone. Based on these conditions, this program aims to educate the society in understanding and applying the green building concept that can prevent the spread of the Covid-19. It is carried out in Peurada, Syiah Kuala District, Banda Aceh. The team conducted a survey on the healthy home concept under government regulation, namely Indonesian Ministry of Health regulation; No. 829/Menkes/SK/VII/1999 by using a scale to effort on the understanding level and application of the green building concept. The respondents were 16 people, the results of the survey showed that the people in Peurada have an understanding level of the green building concept for the prevention of Covid-19 reaching 91.8 % and 82.92% were implemented the concept. Based on this, stated that the people in Peurada had understood and applied the concept of green building in an effort to prevent Covid-19.Keywords: Green building, Socialization, Healthy home.